Adjustment Speed of Debt Maturity: Evidence From Financial Crises in East Asia - Tekin, Hasan; Polat, Ali Yavuz (Bank Indonesia Institute, 2021)
We investigate the change in adjustment speed of debt maturity for East Asian firms between 1990 and 2017 by including two exogenous shocks: the Asian Financial Crisis 1997-1998 (AFC) and the Global Financial Crisis 2007-2009 (GFC). We employ the least square dummy variable correction and find that East Asian firms have a slower adjustment of long-term debt over time. Besides, the decrease in adjustment speed of long-term debt after the GFC is more compared to the decrease after the AFC. Further analysis shows the optimal debt maturity differs across countries and industries. Another important implication of our results is that firms in high governance countries are more likely to close the gap between the actual and target debt maturity in time. Overall, debt holders and investors should consider financial uncertainties. © 2025 Elsevier B.V., All rights reserved.
Keywords: Adjustment Speed; Asian Crisis; Debt Maturity; East Asia; Global Financial Crisis